Pelaksanaan Misi Allah dalam Konteks Keberagaman Budaya di Indonesia - Sigit Wijoyo (Sekolah Tinggi Teologi Kalimantan, 2021)
The implementation of God's mission in the context of cultural diversity in Indonesia is important to study considering that the church has the responsibility to carry out the Great Commission of the Lord Jesus to the nations. The culturally diverse situation of Indonesian society poses a formidable challenge for evangelists because they cannot apply one specific method that can be applied to the entire community. Some churches still apply the mission model inherited by Zending. The Colonial Model is considered less effective due to the growing culture of Indonesian society. Therefore, flexible mission implementation principles are needed, according to the context of society in Indonesia without compromising the biblical meaning of the gospel. This article was compiled by examining the facts of the cultural life of the Indonesian people who are diverse in culture and examining the word of God which contains teachings on the principle of preaching the gospel to all nations. The research process in this article is carried out by conducting library research on the condition of cultural diversity in Indonesia and examining relevant biblical records in carrying out missions in Indonesia. The result is a mission implementation model that takes into account the cultural context, a christocentric mission without losing the Indonesian values of the local community.Pelaksanaan misi Allah dalam konteks keragaman budaya di Indonesia penting dipelajari mengingat gereja memiliki tanggungjawab menjalankan Amanat Agung Tuhan Yesus kepada bangsa-bangsa. Keadaan masyarakat Indonesia yang beragam budaya, merupakan tantangan yang berat bagi para pemberita injil karena mereka tidak dapat menerapkan satu metode khusus yang dapat dipakai kepada seluruh masyarakat. Beberapa gereja masih menerapkan model misi yang diwariskan oleh Zending. Model Kolonial tersebut dinilai kurang efektif dengan adanya budaya masyarakat Indonesia yang telah berkembang. Oleh karena itu diperlukan prinsip-prinsip pelaksanaan misi yang luwes, sesuai dengan konteks masyarakat di Indonesia tanpa mengurangi makna injil yang alkitabiah. Artikel ini disusun dengan meneliti fakta kehidupan budaya masyarakat Indonesia yang beragam budaya dan meneliti firman Allah yang memuat ajaran tentang prinsip pemberitaan injil bagi segala bangsa. Proses penelitian dalam artikel ini dilakuakan dengan melakukan penelitian kepustakaan tentang kondisi keragaman budaya di Indonesia serta meneliti catatan alkitab yang relevan dalam pelaksanaan misi di Indonessia. Hasilnya adalah model pelaksanaan misi dengan memperhatikan konteks budaya, misi yang kristosentris tanpa menghilangkan nilai-nilai keIndonesiaan masyarakat lokal.